On-Road Visualizations for Suspension Tuning of a Race Car: doi: 10.14456/mijet.2016.4 - Kammuang-lue, Niti; Jenjitsil, Sorranat (Engineering Access, 2016)
The objectives of this study are to investigate and propose a new method of using visualization for measuring the dynamic behavior of a race car which corresponds to the tuning of the suspension system. All investigations were conducted on the race car called the “Student Formula CMU F-712”, which was strictly constructed following the 2012 Formula SAE Rules. The behavior of this race car according to variations of the rear tire’s pressures and rear cambers were visualized to evaluate the optimized suspension system’s setup values. These values were suited for drag and skid-pad events. The type of front and rear suspensions of the race car was unequal length A-arm double wishbone. The vibrating force was transferred through push rods and bell cranks to shock absorbers and springs. Digital still cameras were used to capture the car’s behavior and analyses performed from these pictures. It can be concluded that the on-road visualization is acceptable for measuring the dynamics of the race car corresponded to the tuning of the suspension system. The visualization methods used were the pitch angle of the car during launching and the outside rear camber and roll angle of the car during turning. Results obtained from the visualizations were compared with the results obtained from quantitative and qualitative tests to validate the analysis. It was found that very good agreement was archived.